p21-activated kinase improves cardiac contractility during ischemia-reperfusion concomitant with changes in troponin-T and myosin light chain 2 phosphorylation - Monasky, Michelle M. (American Physiological Society, 2012)
p21-activated kinase 1 (Pak1) is a serine/threonine kinase that activates protein phosphatase 2a, resulting in the dephosphorylation of cardiac proteins and increased myofilament Ca(2+) sensitivity. Emerging evidence indirectly indicates a role for Pak1 in ischemia-reperfusion (I/R), but direct evidence is lacking. We hypothesize that activation of the Pak1 signaling pathway is a cardioprotective mechanism that prevents or reverses the detrimental effects of ischemic injury by inducing posttranslational modifications in myofilament proteins that ultimately improve cardiac contractility following ischemic insult. In the present study, we subjected ex vivo hearts from wild-type (WT) and Pak1-knockout (KO) mice to 20 min of global cardiac ischemia followed by 30 min of reperfusion. In the absence of Pak1, there was an exacerbation of the increased end-diastolic pressure and reduced left ventricular developed pressure occurring after I/R injury. ProQ analysis revealed an increase in troponin-T phosphorylation at baseline in Pak1-KO hearts compared with WT. Significantly decreased myosin light chain 2 (MLC2) phosphorylation in Pak1-KO hearts compared with WT after I/R injury was confirmed by Western immunoblotting. These data indicate that Pak1-KO hearts have reduced recovery of myocardial performance after global I/R injury concomitant with changes in troponin-T and MLC2 phosphorylation. Finally, a protein-protein association between Pak1 and MLC2, and Pak1 and troponin-T, was determined by coimmunoprecipitation. Thus, results of our study provide a basis for targeting a novel pathway, including Pak1, in the therapies for patients with ischemic events.